2014
DOI: 10.1159/000430085
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Daucus carota</i></b> Pentane/Diethyl Ether Fraction Inhibits Motility and Reduces Invasion of Cancer Cells

Abstract: Daucus carota (DC) is a herb used in folklore medicine in Lebanon to treat numerous diseases including cancer. Recent studies in our laboratory on DC oil and its fractions revealed potent anticancer activities in vitro and in vivo. The present study aims to investigate the effect of the most potent DC fraction, pentane/diethyl ether (50:50), on lung, skin, breast and glioblastoma cancer cell motility and invasion. Upon treatment, a pronounced decrease in cancer cell motility was observed in the 4 cell lines. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…It also exhibited potent cytotoxicity against colon (Caco-2, HT-29), breast (MCF-7, MDA-MB-23) [11] and human acute myeloid leukemia cells [13], as well as significant anti-tumor promoting effect against DMBA/TPA skin carcinogenesis in mice [4]. Recently, DCOE was subjected to chromatographic separation and fractions were shown to possess antioxidant, hepatoprotective [14] as well as anticancer activity in vitro [14, 15]. The pentane/diethyl ether fraction (F2) containing a major compound identified as 2-himachalen-6-ol (61.4%), was found to suppress proliferation of HT-29 cells by inducing apoptosis [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also exhibited potent cytotoxicity against colon (Caco-2, HT-29), breast (MCF-7, MDA-MB-23) [11] and human acute myeloid leukemia cells [13], as well as significant anti-tumor promoting effect against DMBA/TPA skin carcinogenesis in mice [4]. Recently, DCOE was subjected to chromatographic separation and fractions were shown to possess antioxidant, hepatoprotective [14] as well as anticancer activity in vitro [14, 15]. The pentane/diethyl ether fraction (F2) containing a major compound identified as 2-himachalen-6-ol (61.4%), was found to suppress proliferation of HT-29 cells by inducing apoptosis [14].…”
Section: Introductionmentioning
confidence: 99%
“…The pentane/diethyl ether fraction (F2) containing a major compound identified as 2-himachalen-6-ol (61.4%), was found to suppress proliferation of HT-29 cells by inducing apoptosis [14]. It also inhibited motility of MDA-MB231 and SF-268 cells and reduced invasion of B16F-10 cells [15]. …”
Section: Introductionmentioning
confidence: 99%
“…The treatment also led to a decrease in cancer cell invasion and an increased cell adhesion. Additionally, the Daucus carota fraction decreased the activation of the ρ-GTPases Rac and CDC42, a finding which may partially explain the decrease in cell motility [100]. The cytotoxic effect of Daucus carota oil extract (DCOE) was studied in acute myeloid leukemia (AML) cells.…”
Section: Pharmacological Effects: Cytotoxic Effectsmentioning
confidence: 99%
“…Fractions F1 (pentane) and F2 (pentane:ether) demonstrated the highest anticancer activity with IC 50 values ranging between 7 and 25 μg/ml (Shebaby et al, 2014;Shebaby et al, 2015a). The F2 fraction was also found to inhibit motility and reduce invasion of cancer cells (Zgheib et al, 2014). Chemical characterization has shown that the major compound (MC) in DCOE (32%) (Shebaby et al, 2013), previously reported as 2-himachalen-6-ol (based on NIST11/Wiley9 Mass-Spectral Database), constitutes 61% of the F2 fraction (Shebaby et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%